Sistem Keamanan Pintu Menggunakan Sensor Reed Switch dengan Notifikasi Discord - Hari, Rizki Dini; Hermanto, Hermanto; Kamdan, Kamdan (Journal of Information System Research (JOSH), 2025)
A security system is a crucial component in creating a safe and conducive school environment. This research aims to design and build a prototype of an automatic door security system at SMPN 1 Warungkiara. The system integrates a reed switch sensor to detect the door's status, along with RFID and fingerprint technology as access authentication media. Security notifications are sent in real-time via the Discord platform using a NodeMCU ESP8266 microcontroller connected to a Wi-Fi network, especially for suspicious activities outside operational hours. The research method employed is qualitative with a case study approach, while the system development applies the prototyping model. The development stages include requirements communication, quick design, prototype construction, and user evaluation. The test results indicate that the system prototype functions well and effectively. The sensor accurately detects the door's status, the authentication process using RFID and fingerprint operates as designed, and notifications to Discord are sent instantly. The implementation of this system is expected to enhance digital security monitoring, minimize risks, and support the creation of a safer and more comfortable teaching and learning process within the school environment.